NILAI-NILAI ISLAM DALAM TRADISI NYOROG DI KAMPUNG PONDOK BENDA KECAMATAN JATIASIH KOTA BEKASI - Ajat Hidayat; Dewi Sarina; Pela Safni; Maulidina Rahmawati; Retna Sari; Alfurqan Alfurqan (Jurnal Ilmiah Sosiologi Agama (JISA), 2021)
The Betawi folks in Pondok Benda Village, Bekasi town continuously perform the Nyorog tradition once hospitable the month of Ramadan and before Eid. they'll send food within the variety of cakes or rice along {side|in conjunction with|beside|at the side of|together with} side dishes to older folks. the aim of this study was to work out the values contained within the Nyorog tradition of the Betawi community in Kampung Pondok Benda, Bekasi town. This study uses a qualitative technique employing a case study approach. information sources were taken from fifteen informants through in-depth interviews consisting of ancient leaders, spiritual leaders, employees, youths, and housewives in Pondok Benda Village, Jatirasa Subdistric, Jatiasih District, Bekasi town. The conclusion is that there square measure four Islamic values within the ancient Nyorog Betawi tradition in Pondok Benda Village, Jatiasih District, Bekasih town that is to 1) respect for older folks, 2) taking care of relationship, 3) moments for giving almsgiving, 4) academic facilities for kids.